Gripping material for exhaust gas purification device and exhaust gas purification device

The gripping material for exhaust gas purifiers, composed of an inorganic fiber molded body without a binder and featuring specific structural characteristics, addresses the issues of surface pressure loss and deformation, ensuring the catalyst support remains securely in place throughout its life cycle.

JP7656992B1Active Publication Date: 2025-04-04MAFTEC CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024228072
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Existing gripping materials for exhaust gas purifiers, particularly those with organic binders, face issues such as reduced surface pressure during initial combustion, deformation during assembly, and decreased gripping force over long-term use, leading to a risk of catalyst support falling out.

Method used

A gripping material made from an inorganic fiber molded body without a binder, featuring needle marks with warp threads extending in the thickness direction, a specific needle mark density, and a defined number of effective warp threads, which provide enhanced resistance to deformation and maintain surface pressure over the life cycle.

Benefits of technology

The proposed gripping material effectively prevents the catalyst support from falling out by maintaining surface pressure and resisting deformation throughout the life cycle, from initial use to long-term operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656992000004
    Figure 0007656992000004
  • Figure 0007656992000005
    Figure 0007656992000005
  • Figure 0007656992000006
    Figure 0007656992000006
Patent Text Reader

Abstract

Provided is a gripping material for an exhaust gas purification device that can prevent a catalyst carrier from falling off from a casing. [Solution] The gripping material for exhaust gas purification equipment includes an inorganic fiber molded body made of inorganic fibers and does not contain a binder. The inorganic fiber molded body has needle marks extending in a thickness direction, and the needle marks include warp threads made of the inorganic fibers extending in the thickness direction, Needle mark density: 8.0 to 18.0 pieces / cm 2 and Effective warp thread count: 2.8-6.0 threads / cm 2 and The effective warp threads refer to all warp threads protruding from one peeled surface and the other peeled surface within an area of ​​50 mm x 50 mm when the peeling method described below is carried out, and have a diameter of 100 μm or more and a protruding length of 2 mm or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a gripping material for an exhaust gas purification device and an exhaust gas purification device. [Background technology]

[0002] Inorganic fiber molded products obtained by forming inorganic fibers, such as ceramic fibers, into a mat shape are used in products exposed to high temperatures, such as industrial insulation materials, fireproofing materials, packing materials, etc. In recent years, the inorganic fiber molded products have also been used as gripping materials (hereinafter also referred to as "gripping materials") for automobile exhaust gas purification devices.

[0003] Patent Document 1 discloses a gripping sealant disposed between a catalyst carrier in a catalytic converter for purifying exhaust gas and a shell covering the outside of the catalyst carrier. This gripping sealant is made by attaching a binder such as an organic binder to a mat-like material made of inorganic fibers arranged in a mat shape.

[0004] In addition, in the manufacture of exhaust gas purification devices for automobiles, it is known to place an assembly (hereinafter also referred to as "assembly") in which a retaining material is wound around a catalyst carrier, into a casing by press fitting. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4042305 Summary of the Invention [Problem to be solved by the invention]

[0006] In the grip seal material described in Patent Document 1, the organic binder dissolves during the initial combustion. At this time, the organic binder functions as a lubricant, which may reduce the surface pressure of the grip seal material. Therefore, in the grip seal material described in Patent Document 1, there is a risk that the catalyst carrier will fall off during the initial combustion.

[0007] It is also known that the gripping material deforms when the assembly is press-fitted into the casing. If the amount of deformation increases, the effective area of ​​the gripping material that contributes to the force gripping the catalyst carrier decreases. As a result, the catalyst carrier may fall off.

[0008] Furthermore, it is known that when the holding material is used for a long period of time, the surface pressure of the holding material, which contributes to the force for holding the catalyst carrier, decreases, so that the catalyst carrier may fall off after a long period of use.

[0009] In view of the above, one example of the object of the present invention is to provide a holding material for an exhaust gas purification device, which can suppress the catalyst carrier from falling off from the casing throughout the entire life cycle, from immediately after the start of use to after long-term use, and an exhaust gas purification device. Other objects of the present invention will become apparent from the description of this specification. [Means for solving the problem]

[0010] The present disclosure includes, for example, the subject matter described below.

[0011] Section 1. A gripping material for an exhaust gas purification device, The present invention provides an inorganic fiber molded body that is made of inorganic fibers and does not contain a binder, the inorganic fiber molded body has needle marks extending in a thickness direction, and the needle marks include warp threads made of the inorganic fibers extending in the thickness direction; Needle mark density: 8.0 to 18.0 pieces / cm 2 and Effective warp thread count: 2.8-6.0 threads / cm 2 and The effective warp threads refer to warp threads that have a diameter of 100 μm or more and a protruding length of 2 mm or more among all warp threads protruding from one peeled surface and the other peeled surface within an area of ​​50 mm x 50 mm when the peeling method described below is carried out in a gripping material for exhaust gas purification equipment. <Removal method> A test piece 50 mm wide and 150 mm long is cut out from the inorganic fiber molded body. A 30 mm deep cut is then made in the center of the thickness of one end of the test piece, and both ends formed by the cut are supported by a jig and then set in a tensile tester. The test piece is torn in two by pulling both ends in opposite thickness directions at a speed of 500 mm / min. Section 2. The total volume of the effective warp yarn is 6.5 to 10.0 m m 3 / cm 2 Item 2. A gripping material for an exhaust gas purification device according to item 1, Section 3. Basis weight: 1000~2000g / m 2 3. The exhaust gas purification device gripping material according to item 1 or 2, Section 4. The average volume per effective warp thread is 1.5 to 4.0 m m 3 The gripping material for an exhaust gas purification device according to any one of items 1 to 3, wherein the gripping material is one of the above items 1 to 3. Section 5. 5. A gripping material for an exhaust gas purification device according to any one of items 1 to 4, which has a residual surface pressure of 30 kPa or more after a high-temperature cycle. Section 6. A catalyst support; A casing that covers the outside of the catalyst carrier; A holding material for an exhaust gas purification device according to any one of items 1 to 5, which is disposed between the catalyst carrier and the casing; An exhaust gas purification device comprising: Effect of the Invention

[0012] According to the present disclosure, there is provided a holding material for an exhaust gas purification device, which can suppress the catalyst support from falling off from a casing throughout the entire life cycle, from immediately after the start of use to after long-term use, and an exhaust gas purification device. [Brief description of the drawings]

[0013] [Figure 1] 6A to 6D are explanatory diagrams showing the steps of press-fitting the catalyst carrier wrapped with a retaining material into a casing. [Diagram 2] FIG. 1 is an explanatory diagram of a test piece with a notch. [Diagram 3] FIG. [Figure 4] (A) A partial schematic cross-sectional view showing the force applied to the gripping material when the assembly of Fig. 1 is pressed into a casing. (B) A partial schematic cross-sectional view showing the deformation of the gripping material when an assembly having a gripping material with a small number of effective warp threads is pressed into a casing. (C) A partial schematic cross-sectional view showing the deformation of the gripping material when an assembly having a gripping material with a large number of effective warp threads is pressed into a casing. [Diagram 5] 1A is a partial cross-sectional side view of the assembly before press-fitting, and FIG.1B is a partial cross-sectional side view of the assembly after the holding material 1 has been deformed relative to the catalyst carrier 2 by press-fitting. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] As used herein, nouns without numerical qualification are intended to include both the singular and the plural, unless otherwise expressly stated in the specification or clearly contradicted by the context.

[0015] In this specification, the term "comprises" is a concept that encompasses "consists essentially of" and "consists of only".

[0016] In the numerical ranges described in stages in this specification, the upper or lower limit of a certain numerical range can be arbitrarily combined with the upper or lower limit of another numerical range. In addition, in the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with a value shown in an example or a value that can be unambiguously derived from an example. Furthermore, in this specification, a numerical value connected with "~" means a numerical range that includes the numerical values ​​before and after "~" as the lower and upper limits.

[0017] The following describes the embodiments included in the present disclosure in further detail. Note that the embodiments described below are representative examples of the present disclosure and do not limit the scope of the invention.

[0018] [Gripping material for exhaust gas purification equipment] As shown in Fig. 1(A)-(D), the gripping material 1 for exhaust gas purification device of the present disclosure (hereinafter also referred to as "gripping material 1") is housed in a metal casing 6 in a state of an assembly 3 in which the gripping material 1 is wound around a catalyst carrier 2. The gripping material 1 is disposed between the catalyst carrier 2 and the casing 6. The gripping material 1 grips the catalyst carrier 2 as a cushioning material for the catalyst carrier 2. The gripping material 1 is obtained by subjecting the inorganic fiber molded body of the present disclosure to die cutting or the like. As shown in Fig. 1(A), the gripping material 1 has long sides 1g and 1h that are substantially linear and have substantially the same length, and short sides 1j and 1k that connect the ends of the long sides 1g and 1h, respectively. The short side 1j has straight parts on both sides and a protruding part 1m that is sandwiched between the straight parts and protrudes outward from the straight parts and is defined by three substantially straight sides. The short side 1k has straight portions on both sides and a recessed portion 1n that is sandwiched between the straight portions and protrudes inward from the straight portions and is defined by three substantially straight sides.

[0019] In the present disclosure, the characteristics of the holding material 1 are the same as the characteristics of the inorganic fiber molded body. Therefore, hereinafter, when describing the characteristics of the holding material 1, the characteristics of the inorganic fiber molded body may be used.

[0020] The gripping material 1 for an exhaust gas purification device according to the present disclosure includes an inorganic fiber molded body made of inorganic fibers and does not include a binder. The inorganic fiber molded body has needle marks extending in the thickness direction, In the needle marks, warp threads made of the inorganic fibers are present and extend in the thickness direction, Needle mark density: 8.0 to 18.0 pieces / cm 2 and Effective warp thread count: 2.8-6.0 threads / cm 2 and The effective warp threads refer to all warp threads protruding from one peeled surface and the other peeled surface within an area of ​​50 mm x 50 mm when the peeling method described below is carried out, and have a diameter of 100 μm or more and a protruding length of 2 mm or more.

[0021] <Removal method> A test piece 10 with a width of 50 mm and a length of 150 mm is punched out from the inorganic fiber molded body. Next, a cut of 30 mm depth is made in the center of the thickness of one end face 10e of this test piece 1 as shown in Fig. 2. Next, as shown in Fig. 3, both ends formed by the cut are supported by a gripping jig 12 and then set in a tensile tester. The both ends are pulled in opposite thickness directions at a speed of 500 mm / min to split into two.

[0022] <Inorganic fiber molded body> In one embodiment of the present disclosure, the inorganic fiber molded body is obtained by firing a molded body of an inorganic fiber precursor. In one embodiment of the present disclosure, the molded body of an inorganic fiber precursor is obtained by performing a needling treatment on a laminated sheet. In one embodiment of the present disclosure, the laminated sheet is obtained by laminating thin sheets. In one embodiment of the present disclosure, the thin sheet is obtained by collecting inorganic fiber precursors. In one embodiment of the present disclosure, the inorganic fiber precursor is obtained by spinning a spinning solution by a blowing method. The inorganic fiber molded body is in a mat shape having a predetermined thickness. Hereinafter, a surface perpendicular to the thickness direction of the inorganic fiber molded body may be referred to as a mat surface. In addition, a side surface (surface in the thickness direction) perpendicular to the mat surface of the inorganic fiber molded body may be referred to as an end surface.

[0023] <Inorganic fibers> The inorganic fibers constituting the inorganic fiber molded product of the present disclosure are not particularly limited and include single or composite fibers of silica, alumina / silica, and zirconia, spinel, titania, etc. containing these, but alumina / silica fibers, especially crystalline alumina / silica fibers, are particularly preferred. The alumina / silica composition ratio of the alumina / silica fibers is preferably in the range of 60-95 / 40-5 by weight, more preferably 70-84 / 30-16, and particularly preferably 70-76 / 30-24.

[0024] In addition, the inorganic fibers are preferably short fibers. The fiber length of the inorganic fibers is not particularly limited, but is preferably 1 mm or more and 1000 mm or less, more preferably 30 mm or more and 800 mm or less. The average fiber diameter of the inorganic fibers is preferably 3 to 10 μm, and more preferably 5 to 8 μm. If the average fiber diameter of the inorganic fibers is 8 μm or less, it is preferable because the inorganic fiber molded product has a moderate repulsive force. If the average fiber diameter of the inorganic fibers is 5 μm or more, it is preferable because the amount of dust suspended in the air can be suppressed.

[0025] <Basis weight and thickness of inorganic fiber molded body> The basis weight (mass per unit area) of the inorganic fiber molded body of the present disclosure is determined appropriately depending on the application, but is preferably 1000 g / m 2 More preferably, 1200 g / m 2 The basis weight of the inorganic fiber molded body of the present disclosure is 1000 to 2000 g / m2 in order to obtain a holding material 1 capable of suppressing the catalyst carrier 2 from falling off from the casing 6 throughout the entire life cycle. 2 It is preferable that the thickness is 1000 to 1800 g / m 2 More preferably, it is 1200 to 1800 g / m 2 It is more preferable that:

[0026] The inorganic fiber molded article of the present disclosure has a thickness of preferably 3 mm or more, more preferably 5 mm or more. Also, the inorganic fiber molded article of the present disclosure has a thickness of preferably 40 mm or less, more preferably 30 mm or less, even more preferably 25 mm or less, and particularly preferably 23 mm or less.

[0027] For example, Figures 1(A)-(D) show the steps of press-fitting assembly 3 into casing 6. Figure 1(A) shows the step of preparing holding material 1 and catalyst carrier 2. Figure 1(B) shows the step of preparing assembly 3 in which holding material 1 is wound around catalyst carrier 2 and the holding material 1 is fixed with fixing tape 4 or the like. Figure 1(C) shows the step of press-fitting assembly 3 into casing 6 using jig 7. Figure 1(D) shows the step of completing exhaust gas purification device 8 including catalyst carrier 2, casing 6 covering the outside of catalyst carrier 2, and holding material 1 arranged between catalyst carrier 2 and casing 6.

[0028] The larger the basis weight or thickness of the inorganic fiber molding of the present disclosure, the greater the amount of deformation of the holding material 1 tends to be when the assembly 3 is pressed into it. On the other hand, in order to prevent the catalyst carrier 2 from falling off when the assembly 3 is pressed into the casing 6, it is preferable that the amount of deformation of the holding material 1 is small.

[0029] The basis weight and thickness of the inorganic fiber molded body can be set within the above range by adjusting the amount of fiber per unit area when stacking the aggregate of inorganic fiber precursors (hereinafter also referred to as "thin sheet") constituting the inorganic fiber molded body with a folding device. The inorganic fiber molded body of the present disclosure may be of a single structure or a structure in which multiple inorganic fiber molded bodies are bonded together, but is preferably of a single structure from the viewpoints of handleability and peel strength at the bonding interface.

[0030] <Needle mark density> <Method for measuring needle mark density> In one embodiment of the present disclosure, the needle mark density of an inorganic fiber molded body is determined by the unit area (1 cm ) of the matte surface of the inorganic fiber molded body (a molded body of an inorganic fiber precursor that has been fired). 2 ) means the number of needle marks per

[0031] When visible light is applied to the matte surface of an inorganic fiber molding after the above-mentioned peeling method has been carried out, the amount of light transmitted through the needle marks is greater than the amount of light transmitted through areas other than the needle marks, so the transmitted light is observed as light spots on the peeled surface. The number of light spots and warp threads due to transmission through the peeled surface is counted, and the needle mark density is calculated by dividing the sum of the number of light spots and the number of warp threads by the area.

[0032] That is, visible light is applied to one side of the inorganic fiber molding, the number of light spots and warp threads caused by light passing through the peeled surface is counted, and the needle mark density is calculated by dividing the sum of the number of light spots and the number of warp threads by the area.

[0033] <Preferable range of needle mark density> In the present disclosure, the unit area (1 cm ) of the matte surface of the inorganic fiber molded body is 2 The needle mark density, which is the number of needle marks per cm, is 8.0 to 18.0 marks / cm on average across the entire mat surface. 2 Regarding the needle mark density, there is a trade-off between the likelihood of deformation of the holding material 1 during press-fitting and the level of residual surface pressure of the holding material 1 after high-temperature cycles. 2 If the density is less than 18.0 needle marks / cm, the deformation of the gripping material 1 during press-fitting will be large. 2 If the pressure exceeds 8.0 to 18.0 pieces / cm, the residual surface pressure of the gripping material 1 after the high-temperature cycle will decrease. 2 The inorganic fiber molded body satisfying the above needle mark density can achieve both resistance to deformation when the holding material 1 is pressed into the casing 6 and high residual surface pressure after the high temperature cycle. Both resistance to deformation when the holding material 1 is pressed into the casing 6 and high residual surface pressure after the high temperature cycle contribute to suppression of the catalyst carrier 2 from falling off the casing 6, so the needle mark density is set to 8.0 to 18.0 pieces / cm. 2 By satisfying the above-mentioned needle mark density, it is possible to suppress the catalyst support 2 from falling off from the casing 6 throughout the entire life cycle.

[0034] <Warp threads> The inorganic fiber molded body of the present disclosure has needle marks formed by a needling process. When a needling process is performed in which needles with barbs are inserted into and removed from a laminated sheet, at least some of the fibers are extended in the approximate thickness direction by the needles at the locations where the needles are inserted and removed. The bundles of inorganic fibers formed in the approximate thickness direction inside the inorganic fiber molded body by this needling process are called warp threads.

[0035] <Effective warp threads> In the present disclosure, when the above-mentioned peeling method is carried out, among all the warp threads F (FIG. 3) protruding from both peeled surfaces (one peeled surface 10a and the other peeled surface 10b) per unit area (50 mm×50 mm), those having a diameter of 100 μm or more and a protruding length of 2 mm or more are defined as effective warp threads. The unit area (50 mm×50 mm) for measuring the various values ​​related to the warp threads F is an arbitrary region of the test piece 10 (150 mm×50 mm), excluding the part where a 30 mm deep cut is made in the center of the thickness.

[0036] The effective warp threads have a diameter and length that act to prevent deformation when the holding material 1 is pressed in and to adjust the residual surface pressure after a high-temperature cycle.

[0037] <Number of effective warp threads> In the inorganic fiber molded product of the present disclosure, the number of effective warp threads is 2.8 to 6.0 threads / cm 2 It is.

[0038] Effective warp thread count is 2.8 threads / cm 2 If the number of effective warp threads is less than 6.0 threads / cm, the gripping material 1 is likely to deform when pressed in. 2 If the number of effective warp threads exceeds 2.8 to 5.0 threads / cm, the residual surface pressure of the holding material 1 after high temperature cycles decreases. 2 Within this range, it is possible to achieve both resistance to deformation of the holding material 1 when pressed in and high residual surface pressure after high temperature cycles.

[0039] Here, referring to FIG. 4(A), as in FIGS. 1(B) to 1(D), the holding material 1 made of an inorganic fiber molded body is wound around the catalyst carrier 2, and a plurality of warp threads extend in the inorganic fiber molded body of the holding material 1. When the assembly 3 is pressed into the casing (reference numeral 6 in FIG. 1(C)), the holding material 1 is subjected to a shear stress indicated by an arrow in FIG. 4(A). As shown in FIG. 4(B), when an inorganic fiber molded body having a small number of effective warp threads 1t is used, the holding material 1 is weak against shear stress, and the holding material 1 is easily deformed when pressed. However, when the number of effective warp threads 1t is small, the restraining force that maintains the thickness of the inorganic fiber molded body is weak, and the surface pressure applied from the holding material 1 to the catalyst carrier 2 is relatively high. On the other hand, as shown in FIG. 4(C), when an inorganic fiber molded body having a large number of effective warp threads 1t is used, the holding material 1 is strong against shear stress, and the holding material 1 is not easily deformed when pressed. However, when the number of effective warp threads 1t is large, the binding force maintaining the thickness of the inorganic fiber molding is strong, and the surface pressure applied from the holding material 1 to the catalyst support 2 is relatively low. The holding material 1 of the present disclosure achieves a trade-off between strength against shear stress (resistance to deformation during pressing) and the level of residual surface pressure after a high-temperature cycle applied to the catalyst support 2, thereby preventing the catalyst support 2 from falling off from the casing 6 throughout its life cycle.

[0040] <Total volume V of effective warp yarn> After carrying out the above peeling method, the number (number) N of effective warp threads protruding from the peeled surface 10a or 10b, the diameter (thickness) D, and the length (protruding length from the peeled surface 10a or 10b) L are each measured with a digital microscope. The measurement magnification of the digital microscope is preferably 10 to 20 times. The length L is the length of the part protruding from the peeled surface 10a or 10b, and a part with a diameter of 100 μm or more is measured. The diameter D is a value measured at approximately the middle part in the length direction of the part protruding from the peeled surface 10a or 10b.

[0041] The total volume V of the effective warp threads in this 50 mm × 50 mm area is the volume of each of the N effective warp threads (πD 2 This is the sum of the calculated values ​​of (L / 4).

[0042] In the inorganic fiber molded product of the present disclosure, the total volume (sum of volumes) V of the effective warp threads is 6.5 to 10.0 mm 3 / cm 2 This range of total volume is preferable in terms of suppressing deformation during pressing and obtaining a holding material 1 having a high residual surface pressure after high temperature cycles. In one embodiment of the present disclosure, the total volume (sum of volumes) V of the effective warp threads is 7.0 to 10.0 mm 3 / cm 2 Within this range, it is possible to achieve both resistance to deformation of the holding material 1 when pressed in and high residual surface pressure after high temperature cycles.

[0043] When the number of effective warp threads is constant, the smaller the total volume V of the effective warp threads of the inorganic fiber molded body, the thinner the effective warp threads, and the weaker the inorganic fiber molded body is against shear stress. Therefore, the holding material 1 is more likely to deform when pressed, but the surface pressure applied by the holding material 1 is relatively high. On the other hand, the larger the total volume V of the effective warp threads of the inorganic fiber molded body, the thicker the effective warp threads are, and the stronger the inorganic fiber molded body is against shear stress. Therefore, the holding material 1 is less likely to deform when pressed, but the surface pressure applied by the holding material 1 is relatively low. In this way, the total volume V of the effective warp threads of the inorganic fiber molded body of the present disclosure also contributes to achieving both the strength of the holding material 1 against shear stress (resistance to deformation when pressed) and the remaining surface pressure after the high-temperature cycle applied to the catalyst carrier 2.

[0044] <Multiple Needle Rate> In the present disclosure, a multiple needling process is performed on a location where needle marks have already been formed, and the needle marks thus formed are referred to as multiple needle marks. The multiple needling ratio (i.e., the number of multiple needle marks) can be adjusted in the needling process, for example, by changing the conveying speed of the laminated sheet. The multiple needling process is an example of a means for thickening the warp yarns. The multiple needling ratio can be calculated by the following formula 1.

[0045]

number

[0046] In the case of multiple needle marks, the warp threads tend to be thicker than in the case of single needle marks. Therefore, the volume of the warp threads in multiple needle marks tends to be larger. In other words, by forming multiple needle marks, it is possible to increase the total volume V of the effective warp threads without increasing the needle mark density. As a result, compared to the case of increasing the needle mark density, it is possible to form stronger warp threads (i.e., stronger restraining force to maintain the thickness of the inorganic fiber molding) without excessively decreasing the residual surface pressure after the high-temperature cycle. As described above, the multiple needling process also contributes to achieving both the strength of the holding material 1 against shear stress (resistance to deformation during pressing) and the high residual surface pressure applied to the catalyst support 2 after the high-temperature cycle.

[0047] <Average volume of effective warp threads per needle mark> The number n of needle marks in the above 50 mm × 50 mm area is measured by the above-mentioned measurement method. The average volume of effective warp threads per needle mark (hereinafter sometimes referred to as "average volume of effective warp threads per needle mark") is calculated by dividing the total volume V calculated by the peeling method by n.

[0048] That is, the average volume of the effective warp threads per needle mark is the sum (total volume) V of the volumes of all effective warp threads present on both peeled surfaces (one peeled surface 1a and the other peeled surface 1b) per unit area (50 mm x 50 mm) when the peeling method is carried out, divided by the number n of needle marks per unit area, V / n. The larger the average volume V / n of the effective warp threads per needle mark, the more effectively the needling process is carried out, and the stronger the effective warp threads (i.e., the stronger the restraining force that maintains the thickness of the inorganic fiber molded body) are formed. The average volume of the effective warp threads per needle mark of the inorganic fiber molded body of the present disclosure also contributes to achieving both the strength of the holding material 1 against shear stress (resistance to deformation during pressing) and the high remaining surface pressure after the high-temperature cycle applied to the catalyst carrier 2.

[0049] The average volume of effective warp threads per needle mark of the inorganic fiber molded body is preferably 0.40 mm 3 More preferably, 0.45 mm or more. 3 The average volume of effective warp threads per needle mark of the inorganic fiber molded product is preferably 1.0 mm 3 Less than 0.95 mm, more preferably 3 The following is the result.

[0050] <Average volume per effective warp thread> The total volume V is divided by the number N of effective warp threads to determine the average volume per effective warp thread (hereinafter, sometimes referred to as "average volume per effective warp thread").

[0051] That is, the average volume per effective warp thread is the sum (total volume) V of the volumes of all effective warp threads present on both peeled surfaces (one peeled surface 1a and the other peeled surface 1b) per unit area (50 mm x 50 mm) when the peeling method is carried out, divided by the number N of effective warp threads in the unit area, V / N. The larger the average volume V / N per effective warp thread in the inorganic fiber molded body, the more effectively the needling process is carried out, and the stronger effective warp threads (i.e., the stronger the binding force that maintains the thickness of the inorganic fiber molded body) are formed. The average volume per effective warp thread of the inorganic fiber molded body of the present disclosure also contributes to achieving both the strength of the holding material 1 against shear stress (resistance to deformation during pressing) and the high remaining surface pressure after a high-temperature cycle applied to the catalyst carrier 2.

[0052] The average volume per effective warp thread of the inorganic fiber molded body is preferably 1.0 mm 3 More preferably, it is 1.5 mm or more. 3 The average volume of each effective warp thread of the inorganic fiber molded product is preferably 4.0 mm 3 Less than 3.5 mm, more preferably 3 The following is the result.

[0053] <Residual surface pressure after high temperature cycle> In the inorganic fiber molded article of the present disclosure, the surface pressure after a high-temperature cycle can be determined by the following measurement test. 3 After compressing for 30 minutes, the upper and lower plates were heated to 600°C, and the GBD was 0.27g / cm when released. 3 , GBD=0.30g / cm 3 The release and compression are repeated 1000 times. At the first release, the GBD is 0.27g / cm 3 ) and the surface pressure at the 1000th release (GBD=0.27g / cm 3 The surface pressure value (kPa) at the 1000th opening is taken as the residual surface pressure after the high temperature cycle (also called the residual surface pressure).

[0054] The inorganic fiber molded body of the present disclosure can maintain an excellent gripping force of the catalyst carrier for a long period of time as the residual surface pressure after the high-temperature cycle is higher. Therefore, the inorganic fiber molded body of the present disclosure has a residual surface pressure of 30 kPa or more after the high-temperature cycle, more preferably 33 kPa or more, and particularly preferably 35 kPa or more. In addition, the higher the residual surface pressure after the high-temperature cycle, the more advantageous it is in that the gripping force can be maintained for a long period of time, but the amount of deformation during pressing generally tends to increase. From the viewpoint of suppressing the amount of deformation during pressing, the residual surface pressure of the inorganic fiber molded body of the present disclosure after the high-temperature cycle is preferably 50 kPa or less, more preferably 45 kPa or less, and particularly preferably 40 kPa or less.

[0055] [Method of manufacturing the gripping material] The gripping material 1 of the present disclosure can be manufactured by a method including a spinning step, a needling step, a baking step, and a punching step, as described below. However, the gripping material 1 of the present disclosure may be manufactured by other methods.

[0056] An example of a manufacturing method for this gripping material will be described below by taking as an example a manufacturing method for an alumina / silica-based fiber molding. However, the gripping material of the present disclosure is not limited to having an alumina / silica-based fiber molding, and as described above, may have a molding made of silica, zirconia, spinel, titania, or a composite fiber thereof.

[0057] <Spinning process> In the spinning step, a spinning solution containing basic aluminum chloride, a silicon compound, an organic polymer as a thickener, and water is spun by a blowing method to obtain a laminated sheet of alumina / silica-based fiber precursor.

[0058] <Preparation of spinning solution> Basic aluminum chloride; Al(OH) 3-x Cl xcan be prepared, for example, by dissolving metallic aluminum in an aqueous solution of hydrochloric acid or aluminum chloride. The value of x in the above chemical formula is usually 0.45 to 0.54, preferably 0.5 to 0.53. As the silicon compound, silica sol is preferably used, but other water-soluble silicon compounds such as tetraethyl silicate and water-soluble siloxane derivatives can also be used.

[0059] The spinning solution preferably has a ratio of aluminum derived from the basic aluminum chloride to silicon derived from the silicon compound, calculated as a weight ratio of Al2O3 to SiO2, of usually 99:1 to 65:35, preferably 99:1 to 70:30, and an aluminum concentration of 170 to 210 g / L.

[0060] If the amount of silicon compounds in the spinning solution is less than the above range, the alumina that constitutes the short fibers tends to turn into α-alumina, and the short fibers tend to become embrittled due to the coarsening of the alumina particles. On the other hand, if the amount of silicon compounds in the spinning solution is more than the above range, the amount of silica (SiO2) produced together with mullite (3Al2O3·2SiO2) increases, and heat resistance tends to decrease.

[0061] Even when the aluminum concentration in the spinning solution is 170 to 210 g / L, the spinning solution has an appropriate viscosity, and short fibers having a predetermined average fiber diameter and a sharp fiber diameter distribution can be obtained. The preferred aluminum concentration in the spinning solution is 180 to 200 g / L.

[0062] The spinning solution is prepared by adding a silicon compound and an organic polymer in amounts that give the above-mentioned Al2O3:SiO2 ratio to an aqueous solution of basic aluminum chloride, and concentrating the solution so that the aluminum concentration falls within the above-mentioned range.

[0063] Blowing Spinning, i.e., fiberization of the spinning solution, is usually carried out by a blowing method in which the spinning solution is supplied into a high-speed spinning air stream, thereby obtaining an alumina / silica-based fiber precursor. The structure of the spinning nozzle used in the above spinning is not particularly limited, but it is preferable to use a structure in which the air stream blown out of the air nozzle and the spinning solution stream pushed out of the spinning solution supply nozzle are parallel flows, and the parallel air flows are sufficiently rectified to come into contact with the spinning solution, as described in Japanese Patent No. 2602460.

[0064] In spinning, it is preferable that a fiber is first formed by sufficiently drawing the spinning solution under conditions in which evaporation of water and decomposition of the spinning solution are suppressed, and then the fiber is promptly dried. For this purpose, it is preferable to change the atmosphere from a state that suppresses evaporation of water to a state that promotes evaporation of water during the process in which the fiber is formed from the spinning solution and reaches the fiber collector.

[0065] The alumina / silica fiber precursor is collected by a fiber collector. The fiber collector is equipped with an endless belt made of wire mesh that is installed at a substantially right angle to the spinning airflow, and the spinning airflow containing the alumina / silica fiber precursor is collided with the endless belt while rotating. This produces a continuous thin sheet of the alumina / silica fiber precursor.

[0066] The basis weight of this thin sheet is preferably 10 to 200 g / m 2 , particularly preferably 30 to 100 g / m 2 To an extent, but not limited to this.

[0067] The thin sheet can be further laminated. Specifically, for example, the thin sheet is continuously drawn out and fed to a folding device, where it is folded to a predetermined width and stacked. At this time, the thin sheet is continuously moved in a direction perpendicular to the folding direction. This allows a laminated sheet to be obtained. By laminating the thin sheets in this way, the basis weight (area weight) of the laminated sheet becomes uniform over the entire sheet. As the folding device, the one described in JP-A-2000-80547 can be used.

[0068] The laminate sheet is formed by laminating thin sheets, preferably 5 or more layers, more preferably 8 or more layers, and particularly preferably 10 to 80 layers, although the number of layers is not limited thereto.

[0069] <Needling process> The laminated sheet obtained by the spinning process is subjected to a needling process in which needles having barbs are inserted and removed. This produces a molded body of an alumina / silica-based fiber precursor. The needling process may be performed from only one side or from both sides. It is preferably performed from both sides. In the needling process, the conveying speed of the laminated sheet is changed to adjust the multiple-needle ratio (multiple-needling process).

[0070] The needles are preferably inserted in a direction perpendicular to the sheet surface of the laminate sheet (a surface perpendicular to the thickness direction of the laminate sheet). The needles are inserted deeper than the center of the laminate sheet in the thickness direction. The needles may be inserted so as to penetrate the laminate sheet in the thickness direction.

[0071] In this way, when the needling process is performed, at least some of the fibers are extended in the approximate thickness direction by the needles at the locations where the needles are inserted and removed. This forms needle marks on the surface of the alumina / silica fiber precursor molded body. A bundle of alumina / silica fibers extending in the approximate thickness direction inside the alumina / silica fiber precursor molded body is called a warp thread. In the case of multiple needle marks, fibers extended in the approximate thickness direction by another needle are added to the already formed warp threads, forming thicker warp threads.

[0072] The needling treatment is carried out in order to adjust the residual surface pressure of the alumina / silica fiber molding after high-temperature cycles and to suppress deformation during pressing by forming warp threads.

[0073] The needle marks may penetrate the alumina / silica fiber precursor compact, or may penetrate from one matte surface and extend so as not to reach the other matte surface.

[0074] <Firing process> The holding material 1 of the present disclosure is preferably an alumina / silica-based fiber molded body obtained by firing a molded body of an alumina / silica-based fiber precursor. The firing after the needling treatment is usually performed at a temperature of 900°C or higher, preferably 1000 to 1300°C. If the firing temperature is 900°C or higher, crystallization proceeds sufficiently, and an alumina / silica-based fiber having excellent strength is obtained, which is preferable. Also, if the firing temperature is 1300°C or lower, the grain growth of the fiber crystals does not proceed too much, and an alumina / silica-based fiber having appropriate strength is obtained, which is preferable.

[0075] <Punching process> After the firing step, the alumina / silica fiber compact is subjected to die cutting or the like to obtain the gripping material 1.

[0076] [Use of gripping material] The application of the gripping material 1 of the present disclosure is not particularly limited, and it is widely used in vehicles / machines in which a catalyst carrier is disposed in a metal casing, such as automobiles and construction vehicles. In particular, the gripping material 1 is useful as a gripping material for an exhaust gas purification device mounted on an automobile.

[0077] Since the inorganic fiber molded body constituting the gripping material 1 of the present disclosure does not contain a binder, the catalyst carrier is less likely to fall off from the gripping material 1 during the initial combustion. In addition, it is possible to eliminate odors caused by the combustion of the organic binder, sensor malfunctions caused by binder components during combustion, and the like. Examples of binders include inorganic binders and organic binders. Examples of inorganic binders include silica sol and / or alumina sol. Examples of organic binders include synthetic rubbers such as acrylic rubber and nitrile rubber; water-soluble polymer compounds such as carboxymethyl cellulose and polyvinyl alcohol; thermoplastic resins, thermosetting resins, and the like.

[0078] [Exhaust gas purification equipment] The exhaust gas purification device includes a catalyst carrier, a metal casing that covers the outside of the catalyst carrier, and a gripping material disposed between the catalyst carrier and the casing. The exhaust gas purification device of the present disclosure uses the gripping material 1 for exhaust gas purification device of the present disclosure as the gripping material. In the exhaust gas purification device of the present disclosure, the amount of deformation of the gripping material 1 during press-in is small, and the residual surface pressure after the high-temperature cycle is high, so that the gripping performance of the catalyst carrier after assembly is also good throughout the entire life cycle.

[0079] There is no particular limitation on the configuration of this exhaust gas purification device itself, and the present disclosure can be applied to various exhaust gas purification devices that include a catalyst carrier, a casing, and a holder for the catalyst carrier. EXAMPLES

[0080] The following examples are intended for illustrative purposes only and are not intended to limit the scope of the present invention in any way.

[0081] The methods for measuring and evaluating various physical properties and characteristics of each of the inorganic fiber molded products produced in the examples and comparative examples are as follows.

[0082] <Removal method> A test piece 50 mm wide and 150 mm long was cut out from the inorganic fiber molded body, and a 30 mm deep cut was made in the center of the thickness of one end face 10e of this test piece 10. As shown in Fig. 2, both ends formed by the cuts were held by gripping jigs 12, and then the test piece 10 was set in a tensile tester and pulled in opposite directions perpendicular to the mat surface at a speed of 500 mm / min to split the test piece 10 in two.

[0083] <Method for measuring needle mark density> In the present disclosure, when the above-mentioned peeling method was carried out, the inorganic fiber molded body was cut into a 50 mm x 50 mm square to prepare a sample, and one side of the inorganic fiber molded body was irradiated with visible light. The number of light spots and warp threads due to transmission to this peeled surface was counted, thereby counting the number of all needle marks per unit area. 2 The number of needle marks per 10 mm was defined as the needle mark density.

[0084] <Multiple Needle Rate> The multiple needle rate was calculated by the above formula 1. Here, the actual needle mark density is an actual measurement value obtained by the above-mentioned needle mark density measurement method, and the theoretical needle mark density is a theoretical value of the needle mark density calculated on the assumption that there are no multiple needle marks.

[0085] <Number of effective warp threads> In the present disclosure, when the above-mentioned peeling method is carried out, among all the warp threads F (FIG. 3) protruding from both peeled surfaces (one peeled surface 10a and the other peeled surface 10b) per unit area (50 mm×50 mm), those having a diameter of 100 μm or more and a protruding length of 2 mm or more are regarded as effective warp threads, and the number of such effective warp threads is counted. The unit area (50 mm×50 mm) for measuring the values ​​related to the warp threads is an arbitrary region of the test piece 10 (150 mm×50 mm), excluding the part where a 30 mm deep cut is made in the center of the thickness.

[0086] <Total volume V of effective warp yarn> After carrying out the above peeling method, of all the warp threads F (FIG. 3) protruding from both peeled surfaces (one peeled surface 10a and the other peeled surface 10b) per unit area (50 mm×50 mm), those with a diameter of 100 μm or more and a protruding length of 2 mm or more were determined as effective warp threads in that area. Their number (number of threads), diameter (thickness) and length were measured, and the total volume of the effective warp threads was calculated. The diameter, length and number of the above effective warp threads were measured by observing the peeled surface with a digital microscope (Keyence Corporation, VHX-5000) (magnification: 10x).

[0087] <Average volume of effective warp threads per needle mark> The average volume of effective warp threads per needle mark was calculated as V / n, which is the sum (total volume) V of the volumes of all effective warp threads present on both peeled surfaces (one peeled surface and the other peeled surface) per unit area (50 mm x 50 mm) when the above-mentioned peeling method was carried out, divided by the number n of needle marks per unit area.

[0088] <Average volume per effective warp thread> The total volume V was divided by the number N of effective warp threads to determine the average volume per effective warp thread.

[0089] <Amount of organic binder> The amount of the organic binder was calculated from the ratio of the weight of the organic binder to the weight of the inorganic fiber molded body (total weight of inorganic fibers and organic binder).

[0090] <Hot removal test> The GBD of the inorganic fiber compact after pressing is 0.36g / cm 3 The sizes of the catalyst support and SUS pipe are selected so that the inorganic fiber molded body is wound around the catalyst support, and the assembly is pressed into the SUS pipe. While pressing this catalyst support at a speed of 0.05 mm / min, after 40 minutes the catalyst support is heated at 10°C / min. The average value of the removal load at room temperature from 30 to 40 minutes after the start of the test and the minimum value of the removal load during the temperature rise were recorded, and the load reduction rate was calculated using the following formula 2. The removal load is a value measured by a load cell.

[0091]

number

[0092] <Room temperature compression test> GBD=0.3 In the room temperature compression test, the GBD of the inorganic fiber compact after compression was 0.30g / cm 3 The sizes of the catalyst carrier and SUS pipe are selected so that the size is such that the inorganic fiber molded body is wound around the catalyst carrier. When the inorganic fiber molded body is wound around the catalyst carrier, the inorganic fiber molded body is aligned with the bottom end of the catalyst carrier. After winding, the distance from the top end of the inorganic fiber molded body to the top end of the catalyst carrier is measured at five points in the circumferential direction on both the outer circumferential side (A) and the inner circumferential side (B) of the inorganic fiber molded body. In addition, the distance from the bottom end of the inorganic fiber molded body to the bottom end of the catalyst carrier is measured at five points in the circumferential direction on the inner circumferential side (C). After the measurement, the catalyst carrier wrapped around the inorganic fiber molded body is pressed into the SUS pipe using a jig. After pressing is completed, the distance from the top of the inorganic fiber molded body to the top of the catalyst carrier is measured again at five points in the circumferential direction on the outer periphery side (A') of the mat and the inner periphery side (B') of the mat. In addition, the distance from the bottom of the inorganic fiber molded body to the bottom of the catalyst carrier is measured at five points on the inner periphery side (C') of the inorganic fiber molded body.

[0093] As an example only, Figure 5(A) is a partial schematic cross-sectional view of an assembly 3 before pressing, in which a holding material 1 made of an inorganic fiber molding is wound around a catalyst support 2, and Figure 5(B) is a partial schematic cross-sectional view of the assembly 3 after pressing is completed. The measurement results were evaluated using the following formula. Deformation amount = (B'-A')-(BA) Elongation = (B'-C')-(BC) Total deformation amount = deformation amount + elongation amount

[0094] <Effective area> The effective area is calculated by multiplying the effective height by the length of the gripping material. Using the example of Fig. 5(B) as an example, the effective height (H in Fig. 5(B)) means the distance from the top end of the inner circumferential side (the side in contact with the catalyst carrier 2) of the gripping material 1 to the bottom end of the outer circumferential side (the side in contact with the casing) of the gripping material 1 after the assembly 3 is pressed into the casing. The length of the gripping material 1 is the circumferential length of the inner circumferential surface of the gripping material 1 in the assembled state.

[0095] <Room temperature compression test> GBD=0.4 The above-mentioned cold indentation test was carried out at GBD=0.4.

[0096] <Method for measuring residual surface pressure> The residual surface pressure was determined by the following method.

[0097] After compressing the inorganic fiber molded body for 30 minutes at GBD (bulk density) = 0.30, the upper and lower plates were heated to 600 °C, and the release and compression were repeated 1000 times with GBD = 0.27 when released and GBD = 0.30 when compressed. The surface pressure value at the first release (GBD = 0.27) and the surface pressure value at the 1000th release (GBD = 0.27) were measured.

[0098] The surface pressure value (kPa) at the 1000th opening was taken as the residual surface pressure (surface pressure after the high-temperature cycle).

[0099] [Example 1] Silica sol was added to an aqueous solution of basic aluminum chloride (aluminum content 165 g / L, Al / Cl = 1.8 (atomic ratio)) so that the final composition of the alumina fiber would be Al2O3:SiO2 = 72:28 (weight ratio). Polyvinyl alcohol was then added and the mixture was concentrated to prepare a spinning solution with a viscosity of 70 poise (25°C) and an alumina / silica content of approximately 35% by weight.

[0100] The spinning solution was spun by the blowing method. A spinning nozzle with the same structure as that shown in FIG. 6 of Japanese Patent No. 2602460 was used as the spinning nozzle. In addition, for fiber collection, a wire mesh endless belt was installed at a substantially right angle to the spinning airflow, and a fiber collector was used in which the spinning airflow containing the alumina / silica fiber precursor was collided with the endless belt while rotating. As a result, the alumina / silica fiber precursor was collected as a continuous sheet (thin sheet).

[0101] The thin sheets were sprayed with a lubricant, and then continuously pulled out and fed to a folding device, where they were folded to a predetermined width and stacked while being continuously moved in a direction perpendicular to the folding direction to form a laminated sheet. The folding device used was a folding device with a structure similar to that described in JP 2000-80547 A.

[0102] In the needling process, a needle punching machine is used to punch the laminated sheet, resulting in a needle mark density of 10.6 punches / cm2 in the alumina / silica fiber compact after firing. 2 The needles were punched to a multi-needle ratio of 58%. As a result, an alumina / silica fiber precursor was obtained.

[0103] The alumina / silica fiber precursor compact was then fired at 1200°C to produce a 1200g / m2 fiber. 2 An inorganic fiber molded body (alumina / silica fiber molded body) made of crystalline alumina / silica fibers was obtained. Firing was performed in a gas furnace at a heating rate of 5°C / min up to 1200°C, and after holding at 1200°C for 30 minutes, it was naturally cooled. This inorganic fiber molded body was not impregnated with a binder.

[0104] The composition ratio of this crystalline alumina / silica-based fiber was alumina / silica = 72 / 28 (weight ratio), and the average fiber diameter of the crystalline alumina / silica-based fiber (average value of 100 fibers) measured by observing the inorganic fiber molding under a microscope was 5.5 μm.

[0105] The measurement results of the obtained inorganic fiber molded product are shown in Table 1.

[0106] [Example 2] Basis weight: 1400g / m 2 , needle mark density 10.0 strokes / cm 2 The same procedure as in Example 1 was followed except that punching was performed so that the multi-needle ratio was 50%.

[0107] [Example 3] Basis weight 1700g / m 2 , needle mark density 14.7 strokes / cm 2 The same procedure as in Example 1 was followed except that punching was performed so that the multi-needle ratio was 45%.

[0108] [Example 4] Basis weight 2000g / m 2 , needle mark density 12.4 strokes / cm 2 The same procedure as in Example 1 was followed except that punching was performed so that the multi-needle ratio was 50%.

[0109] [Comparative Example 1] Needle mark density: 14.1 strokes / cm 2 The procedure was the same as in Example 1, except that punching was performed so that the multi-needle ratio was 40%, and an organic binder was added so that the amount was 3.8% based on the weight of the inorganic fiber molded body.

[0110] [Comparative Example 2] Needle mark density: 4.8 strokes / cm 2 The same procedure as in Example 1 was followed except that punching was performed so that the multi-needle rate was 10%.

[0111] [Comparative Example 3] Basis weight 1700g / m 2 , needle mark density 5.3 strokes / cm 2 The same procedure as in Example 1 was followed except that punching was performed so that the multiple needle rate was 2%.

[0112] [Comparative Example 4] Basis weight 1700g / m 2 , needle mark density 25.9 strokes / cm 2 The same procedure as in Example 1 was followed except that punching was performed so that the multiple needle rate was 9%.

[0113] [Comparative Example 5] Basis weight: 1400g / m 2 , needle mark density 18.8 strokes / cm 2 The same procedure as in Example 1 was followed except that punching was performed so that the multiple needle rate was 3%.

[0114] [Comparative Example 6] Basis weight 1275g / m 2 , needle mark density 39.7 strokes / cm 2 The same procedure as in Example 1 was carried out except that punching was carried out so that the multiple needle rate was 0%.

[0115] [Table 1]

[0116] As shown in Table 1, the inorganic fiber moldings of Examples 1 to 4 had an appropriate needle mark density and an appropriate number of effective warp threads, and therefore had a small overall deformation during pressing in a room temperature pressing test, maintained residual surface pressure after a high temperature cycle, and had a small load reduction rate in a hot removal test.

[0117] The inorganic fiber molding of Comparative Example 1 contained an organic binder, and therefore had a large load loss rate in the hot extraction test. If the inorganic fiber molding of Comparative Example 1 is used in an automobile, there is a high possibility that the catalyst support will fall off during the first combustion.

[0118] The inorganic fiber molded body of Comparative Example 2 had a lower needle mark density than that of the inorganic fiber molded body of Example 1 of the same basis weight, and also had a smaller number of effective warp threads than that of the inorganic fiber molded body of Example 1 of the same basis weight, so the total deformation amount in the room temperature pressing test was large. The total deformation amount was larger as the GBD increased. If the total deformation amount is large, the effective area is reduced, so the force for holding the catalyst support is reduced. Therefore, when the inorganic fiber molded body of Comparative Example 2 is used, there is a high possibility that the catalyst support will fall off.

[0119] The inorganic fiber molding of Comparative Example 3 had a lower needle mark density than that of the inorganic fiber molding of Example 3 of the same basis weight, and also had a smaller number of effective warp threads than that of the inorganic fiber molding of Example 3 of the same basis weight, so the total deformation amount in the room temperature pressing test was large. If the total deformation amount is large, the effective area is reduced, and the force for holding the catalyst carrier is reduced. Therefore, when the inorganic fiber molding of Comparative Example 3 is used, there is a high possibility that the catalyst carrier will fall off.

[0120] The inorganic fiber molding of Comparative Example 4 had a higher needle mark density than the inorganic fiber molding of Example 3 with the same basis weight, and therefore had a smaller residual surface pressure. Because the residual surface pressure was small, when the inorganic fiber molding of Comparative Example 4 was used, there was a high possibility of it falling off during long-term use.

[0121] The inorganic fiber molding of Comparative Example 5 had a larger number of effective warp threads and a higher needle mark density than the inorganic fiber molding of Example 2 of the same basis weight, and therefore had a smaller residual surface pressure. Because the residual surface pressure was small, when the inorganic fiber molding of Comparative Example 5 was used, there was a high possibility of it falling off during long-term use.

[0122] The inorganic fiber molding of Comparative Example 6 had a larger number of effective warp threads and a higher needle mark density than the inorganic fiber molding of Example 1 of similar basis weight, and therefore had a smaller residual surface pressure. Because the residual surface pressure was small, when the inorganic fiber molding of Comparative Example 6 was used, there was a high possibility of it falling off during long-term use. [Explanation of symbols]

[0123] 2...catalyst support, 3...gripping material for exhaust gas purification device, 6...casing, 8...exhaust gas purification device, 10...test piece, 10e...end surface, 12...gripping jig.

Claims

1. A gripping material for an exhaust gas purification device, The present invention provides an inorganic fiber molded body that is made of inorganic fibers and does not contain a binder, the inorganic fiber molded body has needle marks extending in a thickness direction, and the needle marks include warp threads made of the inorganic fibers extending in the thickness direction; Needle mark density: 8.0 to 18.0 / cm 2 and Effective warp thread count: 2.8 to 6.0 threads / cm 2 and The average volume per effective warp thread is 1.5 to 4.0 mm 3 / thread, The effective warp threads refer to warp threads that have a diameter of 100 μm or more and a protruding length of 2 mm or more among all warp threads protruding from one peeled surface and the other peeled surface within an area of ​​50 mm × 50 mm when the following peeling method is carried out. Gripping material for exhaust gas purification equipment. <Removal method> A test piece 50 mm wide and 150 mm long is punched out from the inorganic fiber molded body. A 30 mm deep cut is then made in the center of the thickness of one end of the test piece, and both ends formed by the cut are supported by a jig and then set in a tensile tester. The test piece is torn in two by pulling both ends in opposite thickness directions at a speed of 500 mm / min.

2. A gripping material for an exhaust gas purification device, comprising: The present invention provides an inorganic fiber molded body that is made of inorganic fibers and does not contain a binder, the inorganic fiber molded body has needle marks extending in a thickness direction, and the needle marks include warp threads made of the inorganic fibers extending in the thickness direction; The density of needle marks is 8.0 to 18.0 marks / cm 2 ; The number of effective warp threads is 2.8 to 6.0 threads / cm 2 ; The residual surface pressure after high temperature cycle is 30 kPa or more, The effective warp threads refer to warp threads that have a diameter of 100 μm or more and a protruding length of 2 mm or more among all warp threads protruding from one peeled surface and the other peeled surface within an area of ​​50 mm × 50 mm when the following peeling method is carried out. Gripping material for exhaust gas purification equipment. <Removal method> A test piece 50 mm wide and 150 mm long is punched out from the inorganic fiber molded body. A 30 mm deep cut is then made in the center of the thickness of one end of the test piece, and both ends formed by the cut are supported by a jig and then set in a tensile tester. The test piece is torn in two by pulling both ends in opposite thickness directions at a speed of 500 mm / min.

3. The total volume of the effective warp threads is 6.5 to 10.0 mm 3 3. The exhaust gas purification device gripping material according to claim 1 or 2, wherein the surface roughness is 1 / cm2.

4. Basis weight: 1000-2000g / m 2 The exhaust gas purification device gripping material according to claim 1 or 2,

5. 2. The exhaust gas purification device mounting material according to claim 1, which has a residual surface pressure of 30 kPa or more after a high-temperature cycle.

6. A catalyst support; A casing that covers the outside of the catalyst carrier; The exhaust gas purification device holding material according to claim 1 or 2, which is disposed between the catalyst carrier and the casing; An exhaust gas purification device comprising:

Citation Information

Patent Citations

  • Inorganic fiber molded body, mat for exhaust gas purification device, and exhaust gas purification device

    JP2021185279A

  • Inorganic fiber molded body, mat for exhaust gas purification device, and exhaust gas purification device

    JP2021185280A

  • Mat for exhaust emission control system and exhaust emission control system

    JP2021185310A

  • Mat material, process for producing the same, muffler and process for manufacturing muffler

    WO2009133613A1

  • Holding seal material for catalytic converter for exhaust gas purification

    JP4042305B2